2015
DOI: 10.1021/acsbiomaterials.5b00179
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Tunable Calcium Phosphate Biomaterials Synthesis and Application in Protein Delivery

Abstract: Calcium phosphates (CaP) are important biomaterials used in tissue engineering and drug delivery, due to their biocompatibility, low toxicity, and osteoconductivity. However, controlling the phase of CaP, especially tricalcium phosphate (TCP), is very challenging under mild conditions, particularly when using one preparation protocol for all CaP phases. It is also crucial to produce these biomaterials economically and reproducibly. Herein, three of the most commonly employed CaP, including beta-tricalcium phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…ACP precipitated from aqueous solution also appears to have a short lifetime [25,27]. In order to avoid hydrolysis, synthetic methods in organic solvents [28], including solvothermal synthesis [7,29], have become popular in recent years. Organic solvents, i.e., alcohols, favor the formation of ACP because their lower dielectric constants than of water.…”
Section: Introductionmentioning
confidence: 99%
“…ACP precipitated from aqueous solution also appears to have a short lifetime [25,27]. In order to avoid hydrolysis, synthetic methods in organic solvents [28], including solvothermal synthesis [7,29], have become popular in recent years. Organic solvents, i.e., alcohols, favor the formation of ACP because their lower dielectric constants than of water.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallite sizes were estimated using the Scherrer’s equation . The crystallinity ( X c ) of the apatite phase can be evaluated base on the equation: X c = ( K A /fwhm), where K A is a constant set at 0.24 and fwhm is the higher half-maximum (in degrees) of (0 0 2) reflection …”
Section: Methodsmentioning
confidence: 99%
“…Tissue-engineered bone is the most promising biomaterial used to repair bone defects and promote the growth of permanent new bone tissue. , Calcium phosphates (CaPs) have attracted significant attention within the research community because of their biocompatibility, osteoconductivity, degradability, and role as a necessary structural component of bone. However, the lack of osteoinductivity of CaPs limits their applicability with respect to clinical usefulness . Many works have shown that growth factors (GFs) such as bone morphogenic protein 2 (BMP-2) can be incorporated into CaPs to enhance osteoinduction.…”
Section: Introductionmentioning
confidence: 99%
“…In order to establish the experimental protocol for loading biologics on CaP nanoparticles, bovine serum albumin (BSA, ≥96%, Sigma-Aldrich, Stockholm, Sweden, MW: 66430.3 g/mol) and bradykinin acetate salt (≥98%, Sigma-Aldrich, Stockholm, Sweden, MW: 1060.2 g/mol) were selected as model protein and peptide, respectively. BSA was selected as model protein because of its stability and its wide application in evaluating sustained drug release systems [55,56], whereas bradykinin is rather small and can act as model for the loading of larger ones. Further on, as a case study LL-37 antimicrobial peptide (LLGDFFRKSKEKIGKEFKRIVQRIKDFLRNLVPRTES, >95%, Innovagen, Lund, Sweden, MW: 4493.3 g/mol) was loaded on CaP nanoparticles and the antibacterial efficiency of the LL-37-CaP nanoconjugates was evaluated.…”
Section: Preparation Of Nanoparticles Suspension and Macromolecules Amentioning
confidence: 99%